Parto instrumentado - como está a formação em Portugal? - Pereira,Joana (2022)
Abstract Introduction and Objectives: Tocology knowledge is crucial in obstetrician's decisions and actions. The aim of this research is to assess the experience of Portuguese Gynecology and Obstetrics residents in performing operative vaginal delivery. Study design, population and methodology: Observational and transversal study with collecting an anonymous online survey with 47 questions, performed to 2nd to 6th year residents of Gynecology and Obstetrics. Results: 82 responses to the survey were obtained. The mean age of the sample was 29.3±0.248 years and 92.7% (n=76) of the participants were female. About half of the participants (53.7%, n=44) were working in a central hospital. The vacuum was the instrument most frequently used by the residents (95.1%). When asked about their level of confidence in performing an instrumented delivery, 6th-year residents (n=20) gave, on average, on a 1 to 9 scale, a score of 4.25±0.56 for the use of forceps and 8.05 ±0.22 for the use of vacuum (p<0.001). In this sample, 90.2% of the residents had the opportunity to undergo practical training in instrumented deliveries during the residency. Regarding maternal morbidity, the main concern using forceps are obstetric anal sphincter injuries (74.4%) and using vacuum are vaginal lacerations (32.9%). Conclusions: This survey allowed to characterize and to assess the residents experience, as well as their limitations, on performing operative vaginal deliveries. The knowledge acquired is essential to adapt and homogenize training plans, whenever needed.